Peningkatan Hasil Belajar Pendidikan Agama Islam Melalui Metode Diskusi di Kelas XII F 6 SMAN 1 Suliki - Rahman, Muhamad Em Nur (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to explore the implementation of cycle-based learning, grounded in constructivist theory, to enhance students' understanding of concepts and skills. The research uses a cyclical approach, with two learning cycles involving continuous improvement based on reflections from each cycle. The results indicate that cycle-based learning positively impacts the enhancement of both cognitive and social skills. Cycle I identified several challenges in students' adaptation to the new method, while Cycle II showed significant improvement in engagement and learning outcomes. This study concludes that cycle-based learning is effective in improving the quality of education and students' collaborative skills.